Sistem Informasi Seleksi Karyawan Berbasis Web Pada PT. Kiyokuni Technologies - Lestari; Muhtajuddin Danny; Amali (Jurnal SIGMA, 2023)
With the development of information technology and the need for human resources in a company. Therefore we need an information system that can facilitate the company in the process of recruitment and selection of employees. PT. Kiyokuni Technologies is a company engaged in the field of electronic parts which is a growing company. Currently the employee selection process is still carried out in writing and using paper. This raises several problems such as applicant data that accumulates, is easily lost and damaged, it takes a long time to carry out the employee selection process and when selecting the HR department, it often encounters problems in determining the results of the selection decisions made by applicants. This research resulted in an employee selection information system design using the waterfall method and Unified Modeling Language (UML) diagrams that can be used as a basis for implementing the employee selection information system to be used as a solution in solving existing problems. Keywords: Employee Selection Information System, UML, Waterfall.